Asymptomatic aortic aneurysm causing right vocal cord palsy and hoarseness: A rare presentation - Rizvi, M. M. (Anesth Essays Res, 2014)
Vocal cord palsy (VCP) presenting as hoarseness of voice can be the first symptom of very serious and sinister common pathologies. But vocal cord palsy resulting from aortic aneurysm is a rare entity and still rarer is the right cord palsy due to aortic aneurysm. We are reporting a rare case in which a 52-year old male smoking for last 30 years having asymptomatic aortic aneurysm presented to us with hoarseness of voice. On Panendoscopy, no local pathology was found and CECT from base of skull to T12 was advised. CECT showed a large aneurysm involving ascending aorta and extending upto abdominal aorta with compression of the bilateral bronchi. CTVS consultation was sought and they advised for regular follow-up only. We are reporting this case to warn both the anaesthetist and the surgeon about the catastrophic complications if they are not alert in handling such cases.